Studies on the Interaction between Model Proteins and Fluorinated Ionic Liquids - Márcia M. S. Alves; Manuel N. Melo; Haydyn D. T. Mertens; Ana B. Pereiro; Margarida Archer (MDPI AG, 2023)
Proteins are inherently unstable, which limits their use as therapeutic agents. However, the use of biocompatible cosolvents or surfactants can help to circumvent this problem through the stabilization of intramolecular and solvent-mediated interactions. Ionic liquids (ILs) have been known to act as cosolvents or surface-active compounds. In the presence of proteins, ILs can have a beneficial effect on their refolding, shelf life, stability, and enzymatic activities. In the work described herein, we used small-angle X-ray scattering (SAXS) to monitor the aggregation of different concentrations of ILs with protein models, lysozyme (Lys) and bovine serum albumin (BSA), and fluorescence microscopy to assess micelle formation of fluorinated ILs (FILs) with Lys. Furthermore, coarse-grained molecular dynamics (CG-MD) simulations provided a better understanding of Lys-FIL interactions. The results showed that the proteins maintain their globular structures in the presence of FILs, with signs of partial unfolding for Lys and compaction for BSA with increased flexibility at higher FIL concentrations. Lys was encapsulated by FIL, thus reinforcing the potential of ILs to be used in the formulation of protein-based pharmaceuticals.